Influences of Chloride Salts on Enzymatic Activity, Lipid Oxidation and Volatile Compounds of Reduced-Sodium Salt Pastırma - Yalınkılıç, Barış; Suncak, Fatma Yağmur Hazar; Kaban, Güzin; Aksu, Muhammet İrfan; Kaya, Mükerrem (MDPI AG, 2025)
The study investigated the effects of chloride salts (control: 100% NaCl, salt mixture I: NaCl/KCl (50/50), salt mixture II: NaCl/KCl/CaCl2 (40/40/20), salt mixture III: NaCl/KCl/CaCl2/MgCl2 (30/40/20/10)) on enzymatic activity, lipid oxidation, and volatile compounds in reduced-sodium salt pastırma, a Turkish dry-cured meat product. Lipid oxidation and instrumental color values were not affected by different salt mixtures. Salt mixtures II and III decreased pH value (p < 0.05). However, the mean pH value did not fall below 5.5 in any sample. The salt mixture treatment had significant effect on water activity, cathepsin B, and cathepsin B + L. In contrast, aw value was under 0.90 in all treatments. The highest mean values for cathepsin B and B + L were determined in the control group with 11.69 ± 2.73 and 85.82 ± 12.65 U g−1 × 10−3 dry matter, respectively. The closest correlation for lipolytic enzyme activities was determined by the mixture II and III groups, while a closer correlation was observed between salt mixtures I and III in terms of proteolytic enzyme activities. With regard to volatile compounds, there was a closer relationship between the control and salt mixture I. As a result, it can be concluded that salt mixture I in reduced-sodium salt pastırma showed closer results to the control group.